Conjugal transfer of macrolide-lincosamide-streptogramin resistance from lactic acid bacteria isolated from food materials. (2022) - Ashwini, M.; Ray, Mousumi; Halami, Prakash M.; Sumana, K.
Abstract: Lactic Acid Bacteria being a reservoir of antimicrobial resistant genes, possibly pose a menace to human and animal health. Therefore, the purpose of this study was to assess the Horizontal Gene Transfer (HGT) of Macrolide-Lincosamide-Streptogramin (MLS) resistance from Lactic Acid Bacterial isolates of idli batter, chicken and sheep intestine viz., Lactobacillus fermentum (I4.16), Enterococcus hairae (C2C) and Enterococcus faecalis (SH7aab) respectively. These isolates being multidrug resistant were used as donor to analyse its transferability of MLS resistant gene to recipients Enterococcus faecalis JH2-2, Lactococcus lactis (T3.11) and Acinetobacter. Among the conjugation protocol used in the study, filter-mating method showed the efficient transfer frequency to obtain transconjugants. For all the conjugation the transconjugants obtained showed the acquisition of MLS resistance. The transfer frequency per recipient ranged between 1.4 × 10 −4 to 3.7 × 10 −5 . The Minimum Inhibitory Concentration of erythromycin and clindamycin increased to 3–4 folds in the recipients after respective conjugation. Altogether, the results procured in this study indicates that the HGT between bacterial strains of food materials develop a vibrant gene pool that confers antibiotic resistance onto native gut microbiota even in the lack of pathogens. This probability of HGT among microbial pool should be considered as a criterion when Lactic Acid Bacteria are screened as starter cultures and probiotics in food industries.